Proceedings of the 12th Asia Pacific Physics Conference (APPC12) 2014
DOI: 10.7566/jpscp.1.017033
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Student Reasoning about Harmonic Motions

Abstract: This study aimed to investigate student reasoning about harmonic oscillations. We conducted a semi-structured interview based on three situations of harmonic motions-(1) a mass attaching to spring and horizontally oscillating without damping, (2) the same situation but vertically oscillating and (3) a mass attaching to spring and oscillating in viscous liquid. Forty-five second-year students taking a vibrations and wave course at Chiang Mai University, Thailand participated in a fifteen-minute interview, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…The highest percentage of misconceptions on item 68.4% of students answered misconceptions about the relationship of spring length to the frequency value. This result is in line with research conducted on 45 students who carried out special classes at the Chiang Mai University of Thailand and provided information that most students reasoned that the mass and spring constant are the same so that the frequency value must remain the same [26]. Students' misconceptions in the medium category are shown in items 1, 3, and 5, and low misconception in items 2, 6, 7, 8, and 9 [27].…”
Section: Diagnosis Of Student Misconceptionssupporting
confidence: 86%
“…The highest percentage of misconceptions on item 68.4% of students answered misconceptions about the relationship of spring length to the frequency value. This result is in line with research conducted on 45 students who carried out special classes at the Chiang Mai University of Thailand and provided information that most students reasoned that the mass and spring constant are the same so that the frequency value must remain the same [26]. Students' misconceptions in the medium category are shown in items 1, 3, and 5, and low misconception in items 2, 6, 7, 8, and 9 [27].…”
Section: Diagnosis Of Student Misconceptionssupporting
confidence: 86%
“…Specifically, Wan et al [6] have found that students confuse period and angular frequency when interpreting periodic functions, including functions for waves, and Turner, Ellis, and Beichner [7] found that students perform much better on a validated test for understanding linear kinematics graphs than on an equivalent test on rotational kinematics graphs. A few less relevant studies have investigated student understanding of concepts that implicitly include some of these three quantities, such as in the study of simple harmonic motion and oscillations [8,9], wave phenomena [10][11][12], and rotations [13].…”
Section: Introductionmentioning
confidence: 99%